Anti-programmed cell death-1 and anti-programmed cell death ligand-1 immune-related liver diseases: from clinical pivotal studies to real-life experience. (1st September 2020) - Vitale, Giovanni; Lamberti, Giuseppe; Comito, Francesca; Di Nunno, Vincenzo; Massari, Francesco; Morelli, Maria Cristina; Ardizzoni, Andrea; Gelsomino, Francesco
ABSTRACT: Introduction: Monoclonal antibodies directed against programmed cell death-1 (anti-PD-1) and its ligand (anti-PD-L1) showed a significant efficacy among different immunogenic metastatic tumors such as melanoma, non-small cell lung cancer (NSCLC), renal cell carcinoma (RCC). Between immune-related adverse events (irAEs) dependent on immune checkpoint inhibitors (ICPIs), immune-related liver diseases are uncommon and a definitive diagnosis is not always feasible. Areas covered: We revised data from phase II/III clinical trials and real-world retrospective analyses on liver-related adverse events induced by anti-PD-1 (nivolumab/pembrolizumab) and anti-PD-L1 (atezolizumab) in advanced cancer populations (melanoma, NSCLC and RCC). Furthermore, we described clinical-pathological patterns of immune-related liver diseases in real-life. Expert opinion: Use of anti-PD-1 and anti-PD-L1 led to a paradigm shift in the management of patients with melanoma, NSCLC and RCC. IrAEs can occur potentially in any tissue, leading to discontinuation of ICPIs, at least in a small proportion of these patients, and to a negative impact on their prognosis. Hepatobiliary immune-related adverse events are underestimated due to inappropriate monitoring. Development of novel diagnostic and therapeutic strategies for cancer patients receiving ICPIs as well as the identification of predictive biomarkers of liver injury could allow a better patients' selection and improve clinical outcomes of immune-related liver diseases.